If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2 = h + 3 Reorder the terms: 2 + x = h + 3 Reorder the terms: 2 + x = 3 + h Solving 2 + x = 3 + h Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 3 + -2 + h Combine like terms: 2 + -2 = 0 0 + x = 3 + -2 + h x = 3 + -2 + h Combine like terms: 3 + -2 = 1 x = 1 + h Simplifying x = 1 + h
| 6x-4=47 | | 25-4x=p-8x | | 3y+9=y+3 | | (x-2)(x+4)=x(x+3)-5x | | 180=(2x+2)+(3x+1) | | 3(4x+5)-2(3x-2)=3x+7 | | t*5-4=16 | | 20+3x-2=x^2-4x | | -4b=3(-4b)+7 | | 180=(8x)+x+90 | | 0.86(3.7-2.3x)=4.9 | | (7n-2)(5n-1)=0 | | 0.86(3.7-2.3x)=49 | | 30a^2+7a=0 | | (5v+7)(2+v)=0 | | g(-4b)=3(-4b)+7 | | 2x^3-8x^2-192x=0 | | 6cos+5tan=0 | | 5r+4r-9r= | | 6cisb+5tan=0 | | 2x=-10-2 | | 180=2x+76 | | 180=2x+76+(5x-2) | | 6(3x+5)-5(x-7)=39 | | c=6+5x | | 7x-3=24x+5 | | 7x-3=24x | | 3x+4+4y=16 | | 16=.25b | | b+2.25=5 | | 16=.25 | | 15w*1.25= |